ArcNLET-Py: An ArcGIS-based nitrogen load estimation toolbox developed using python for ArcGIS pro - Wei Mao; Michael Core; Ming Ye (SoftwareX, 2024)
Onsite Sewage Treatment and Disposal Systems (OSTDS) are privately owned infrastructures that are critical for treating domestic wastewater in the USA. The ArcGIS-based Nitrogen Load Estimation Toolbox (ArcNLET) was developed to estimate nitrogen load from OSTDS to groundwater and surface waterbodies by simulating reactive transport of ammonium and nitrate nitrogen in soils and unconfined groundwater aquifers. Quantifying the load and removal of wastewater effluent requires resources, including data, computational power, and professional expertise that are not always available to state and local government agencies. Here, we discuss the advantages of utilizing a simplified model within a GIS to overcome data restraints, simulate the transport and load of nitrogen, and elaborate on the process of renovating and updating ArcNLET for integration with Python and ArcGIS Pro. ArcNLET-Py has the following modules: Module 0 for pre-processing the SSURGO database, Module 1 for groundwater flow simulation, Module 2 for particle tracking, Module 3 for a Vadose Zone MODel (VZMOD), Module 4 for nitrogen reactive transport modeling, and Module 5 for estimating nitrogen load to groundwater and surface waterbodies. The nitrogen reactions considered in Module 3 and Module 4 include ammonium sorption, ammonium nitrification, and nitrate denitrification in the flow path from OSTDS to surface waterbodies. As a newly introduced module, Module 0 streamlines the preparation of soil data from the SSURGO database, thereby enhancing the ease of use of ArcNLET-Py. An example of using ArcNLET-Py is presented for estimating nitrogen load in the Lakeshore neighborhood of Jacksonville, Florida. This work demonstrates the feasibility of developing complex pollution assessment software in the Python environment of ArcGIS Pro and holds implications for water environment protection.